Facile Alder‐Ene Reactions of Silylallenes Involving an Allenic C(sp2)H Bond. Issue 48 (20th October 2015) - Sabbasani, Venkata R.; Huang, Genping; Xia, Yuanzhi; Lee, Daesung
Abstract: Facile and selective Alder‐ene reactions of silylallenes involving the activation of an allenic C(sp 2 )H over an allylic C(sp 3 )H bond is described. In this ene reaction, the presence of a silyl substituent was found to be critical for the observed reactivity and selectivity since the corresponding alkyl‐substituted allenes show different reaction profiles. Computational studies show that the origin of this unusual reactivity is the lower bond dissociation energy of the α‐C(sp 2 )H bond in silylallenes compared to the corresponding nonsilylated allenes. Abstract : To silylate or not to silylate? An unusually low bond dissociation energy (BDE) for the C(sp 2 )H bond in silylallenes is the origin of its selective participation in Alder‐ene reactions with azodicarboxylate, glyoxalate, and benzyne. DFT calculations show that the BDE of the allenic C(sp 2 )H bond is significantly lower than that of a typical allylic C(sp 3 )H bond, which is the result of the existing silyl group. Nonsilylated allenes engage only their allylic C(sp 3 )H bond in these ene reactions.